EXPLORING TRANSLANGUAGING PRACTICE IN EFL CLASSROOM TALK - Rendi Afriadi; Hamzah Hamzah (English Language and Literature International Conference (ELLiC) Proceedings, 2021)
There have been debates on how different languages should be treated in a language learning class especially in EFL classroom context, where students have limited access to target language use and exposure outside the classroom. The monolingual approach promotes English-only classroom in order to provide students with linguistic input and language arena to which they expose themselves to target language. However, the current trends have voiced challenges to monolingual classroom due to the fact that English-only classroom might seem a bit unrealistic especially for several students and the use of students’ native language potentially helps students during the learning process. Therefore, they suggest that language learning classroom should also consider the use of the non-target languages. Such practice is known as translanguaging, in which teachers and students use their whole language repertoire in the interaction during the learning process. This study attempts to explore how students’ and teachers’ language repertoire is exploited through translanguaging in the classroom talk and what functions it brings to the learning process. To that aim, several meetings of EFL classroom interaction were recorded to obtain the language use from both teacher and student talk. The data from teacher’s and students’ utterances were then analyzed to classify their language repertoire used in their talk and to identify the purposes of the translanguaging. The research findings indicate that teacher’s and students’ language repertoire exploited in EFL classroom talk include the local language, national language, and target language. Local language was mainly used for non-instructional purposes in this case making jokes while local and target language were mainly used for instructional purposes such as explaining material, giving clarification, and managing classroom.